Estrategias de ordenamiento territorial para enfrentar el cambio climático: un análisis de las dinámicas de investigación - Ramírez-Orozco, Alejandro (Revista Científica, 2024)
This study examines research trends regarding land use planning and climate change, evaluating the quantity, quality, and structure of scientific publications. To this effect, a scientometric analysis of 1506 documents was conducted, assessing indicators such as the number of publications by year, author, journal, country, institution, and type. In addition, quality was evaluated through citations and structural analysis, including co-authorship and term cooccurrence. The results show an increase in the number of publications over time, highlighting a rise in interest and international collaboration. Authors such as Dominic Stead and Lain White are the most prolific, while the most active institutions are the Chinese Academy of Sciences and Wageningen University & Research. At the global level, countries from the Global North lead scientific production. Additionally, the quality analysis indicates that specific authors and journals hold significant influence in the field. In conclusion, the study reveals an increasing trend in research on climate change and land use planning, emphasizing the importance of international collaboration and the need for policies, funding, and publishing to facilitate the dissemination of these crucial studies. This study is of great relevance since there is no recent analysis of the research dynamics in the field of planning aimed at climate change.